Integrating Artificial Intelligence in Human Resources Management: A Bibliometric Analysis of Emerging Trends and Influences - Baskara, Dwi Soca; Gunadi, Suyud; Muttaqin, Nabil (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
This study aims to analyze the integration of Artificial Intelligence (AI) in the field of Human Resource Management (HRM) from 2004 to 2024. By measuring productivity, impact, collaboration and research topics, this research tracks the development of the domain. These findings may provide a foundation for future research on the growth of AI-focused HRM research, lead authors, institutions, and emerging themes. Using the Scopus database, 381 relevant documents were identified and analyzed, showing an increase in publications year on year, with significant growth between 2020 and 2023. This shows the transformative impact of AI on HRM. This analysis reveals rapid growth and international collaboration in AI-enabled HRM research, demonstrating significant potential. Future research could explore specific applications of AI, ethical considerations, and long-term impacts on HRM practices.